2011
DOI: 10.1116/1.3602082
|View full text |Cite
|
Sign up to set email alerts
|

Study of stress in tensile nitrogen-plasma-treated multilayer silicon nitride films

Abstract: International audienceThe authors conducted a physico-chemical analysis of tensile sequential-nitrogen-plasma-treated silicon nitride films, which function as stressor liners in complementary metal oxide semiconductor (CMOS) technologies. These films are made of stacked nanometer-thick, plasma-enhanced, chemical vapor-deposited layers which were individually treated with N(2)-plasma, to increase stress. This study allowed us to monitor the evolution of the films' chemical composition and stress as a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…The films were then formed by sequential deposition/plasma treatment steps. A more detailed description of the deposition process of these tensile films can be found in Morin et al 8 Compressive films were monolayer films deposited at low pressure (2 Torr) and increased plasma power (75 W) to improve atomic peening. The deposited thicknesses of both film families range from 130 to 680 nm.…”
Section: Experimental Techniques a Film Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…The films were then formed by sequential deposition/plasma treatment steps. A more detailed description of the deposition process of these tensile films can be found in Morin et al 8 Compressive films were monolayer films deposited at low pressure (2 Torr) and increased plasma power (75 W) to improve atomic peening. The deposited thicknesses of both film families range from 130 to 680 nm.…”
Section: Experimental Techniques a Film Processingmentioning
confidence: 99%
“…Chemical bond types and densities were measured by combining spectroscopic ellipsometry (FX100 ellipsometer from KLA Tencor) and Fourier Transform InfraRed (FTIR) spectroscopy (BIO RAD QS 2200A from Accent). A specific analysis was applied to obtain an overall description of the film chemistry, 8 thus providing quantitative bond concentration results of 10 17 bonds cm À2 with an uncertainty of 60.5. Film density was measured, thanks to a high-precision weighting machine (Mentor SP3 from Metryx).…”
Section: B Physical and Chemical Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other important factors (e.g., precursors, plasma conditions, plasma treatment) which may modulate the stress were not studied. King and Triyoso et al reported that the intrinsic stress of PEALD SiN x films could be modulated to be either compressive or tensile by varying low-frequency power [ 4 , 5 ], which also holds true for PECVD SiN x films [ 122 , 123 ].…”
Section: Current Research Progressmentioning
confidence: 99%
“…With introduction of the 90 nm node geometries the deposition of compressive stressed contact etch stop layers (CESL) for increasing hole mobility and tensile stressed CESL for enhancing electron mobility in dual-stressor liner technology have been introduced in logic device fabrication [1]. For creating highly tensile stressed silicon nitride (SiN) cap layers on NMOSFET, many techniques like in-situ nitrogen plasma treatments [2], multi-layer deposition [3], and subsequent ultraviolet (UV) [4,5] curing cycles have been developed. Conventional UV curing equipment uses broadband lamps at and above 220 nm wavelengths, preferably.…”
Section: Introductionmentioning
confidence: 99%